Analisis Faktor-Faktor yang Mempengaruhi Penghindaran Pajak pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Robby Krisyadi; Novilim Novilim (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
The purpose of this research is to analyze the factors that effect tax avoidance on companies listed in Indonesia Stock Exchange. The factors mentioned as independent variables in this study are profitability, audit quality, fiscal loss compensation, capital intensity, firm size, and leverage. Effective tax rate is used as a benchmark of tax avoidance. Determination of the sample in the study using a purposive sampling method by including companies registered in the IDX period of 2015 to 2019. Data on the annual financial reports of companies that have complete financial information are the criteria for collecting research data. The gathered data are then analyzed using a panel regression method with SPSS and Eviews software. The result showed that profitability and audit quality had a positive significant effect on tax avoidance while fiscal loss compensation had a negative significant effect. Meanwhile, the variables of capital intensity, firm size, and leverage do not have an effect on the tax avoidance.